Marginalized Selfhood of Women in Tehmina Durrani’s Blasphemy - Saleem, Dhobi (Patan Pragya, 2020)
This paper investigates into Durrani’s Blasphemy to scrutinize Heer's marginalized individuality. Heer is forced to marry a man, Pir Sain, with a high position in the society. Hermarriage proves a source of troubles and repression of self-satisfaction. When Heer fails to tolerate severe torture and exploitation, she revolts against patriarchy that pushes the female sex to the margin in the name of religious norms and values. Hence, this article exposes the desperate condition of women and their sufferings in Pakistan as depicted in the novel. The paper questions the system that does not allow women like Heer to make decisions in either household chore, not in the public affairs.